Le Saulchoir on Trial (1932-1943). - Fouilloux, Etienne; Kelly, Patricia (Adelaide : ATF Press, 2022)
February 1942. The world is on fire and bloody. The United States has just entered the war following the aggressive attack on their air and naval base at Pearl Harbour at the beginning of December. The German troops besiege Leningrad and are fighting before Moscow: The Wannsee Conference of 20 January has just established the logistics of the "final solution" for Jews under the ascendancy of the Third Reich. The Japanese seize Singapore on 15 February... No one seems capable of stopping the destructive march of the totalitarian regimes. At the Vatican, however, proceedings follow their course as if nothing was any different: a decree of the Holy Office places on the Index of Prohibited Books two works concerning the definition of theology, outsiders to the noise and violence of a war henceforth worldwide: the Essai sur le probleme theologique (Essay on the theological problem] by the Belgian Dominican Louis Charlier, published in 1938, and the small booklet Uneecole de theologie: le Saulchoir [A school of theology: the Saulchoir], by his French colleague Marie- Dominique Chenu, published privately at the end of the previous year. This book details a ten year history. Etienne Fouilloux gives us here the story of a forgotten or misunderstood episode in the history of the Catholic Church, still struggling with the ghosts of Modernism. Vatican I is still far away and yet it is the whole issue of the renewal of theology that this fascinating book by a great historian highlights.
Description based upon print version of record.
JSTOR
Keywords: Saulchoir (Divinity school) -- History; Saulchoir (Divinity school); Catholic theological seminaries -- France; Séminaires catholiques -- France; History; Christianity; RELIGION; Catholic theological seminaries; France; Electronic books; History